SOME STRUCTURAL PROBLEMS OF FOOTBALL PLAYERS MOTRIC ACTIVITY IN TRAINING AND COMPETITIONAL PROCESS - Dumitru Darjan; Dan Păun; Cătălin Cişmaş (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
During the formative period, there are acquired specific elements of theoretical knowledge in constant link of interdependence with motric skills used in the specific motric activity specialized for the teaching-learning process, from the physical education and the performance activity. In time, from the the beginning of the professional activity, by joining of theory and practice in physical education and sport performance, • we found out some disunities between the real sense of some terminology components used in the theory of motric qualities development and the real sense of practice activity. So, the longest phrase from the motric activities theory, is "to develop force" in the conditional motric skills, when actually is`t only about "strenght". In this communication, we argue for understanding, discriminating and respecting the real sense of concepts "force" and "strenght" given that it supports the claim to which: • in performance sport, for the most sport branches, the important role it has the strenght, not the force.